Subtitling Strategies Of Cultural Word In The Hamka’S Dibawah Lindungan Ka’Bah Movie - Maizal, Ilham; Zulprianto, Zulprianto; Lindawati, Lindawati (Universitas PGRI Sumatera Barat, 2025)
Subtitling is one of the development of translation studies. Subtitling has flourished in a movie. More subtitling means more viewers. The movie industry is growing rapidly but it is dominated by foreign movies with subtitles in Indonesia. The use of English subtitles in Indonesian movies is limited. This study is aimed to analyze subtitling strategies of Cultural Words Di Bawah Lindungan Ka’bah of Hamka streamed on WeTV. The movie is nominated the Best Foreign Language Movie at the 84th Academy Awards. This study belongs to descriptive qualitative research. The spoken languages Indonesian, Arabic, and Minangkabau languages as the sources language and its English subtitling as a target language. This study combines Gottlieb subtitling strategies and Newmark Cultural Translation theories. The results of the research: 1) the subtitling strategies used 7 of 10; expansion 45, transcription 41, transfer 37, imitation 16, paraphrase 4, deletion 2, condensation 1, 2) from 146 subtitles, this study found that the subtitling strategies of cultural words in the Di Bawah Lindungan Ka’bah: Social culture 92, Habbit and Gesture 25, Material Culture 15, Organization, custom and idea 11, and ecology 3. 3)the most subtitling strategies used expansion, 4)the most cultural words used socio culture